Muttersprache im Fremdsprachenunterricht - mehr als ein Ausweichmanöver? - Ciepielewska, Luiza (Glottodidactica, 2008)
The article deals with the role of the native language in a foreign language class. The practical aspects of moderate native language usage are discussed. Using concrete examples, the author discusses the positive influence of a native language on communication during foreign language class.